Vietnamese and Haiku - Vu Quynh Nhu NGUYEN (Gwagyeong Ilboneo Munhak Yeongu, 2019)
This study discusses haiku in relation to Vietnam. In 2007, the first Japanese-Vietnamese haiku contest, held in Ho Chi Minh City, attracted not only Vietnamese scholars of Japanese literature but also members of the general public. Since then, Vietnamese- language haiku has gained in popularity. Many Vietnamese haiku lovers tend to express an interest in the aesthetic sides of the haiku’s short forms, with rare use of the 5-7-5 word structure and linguistic minimalism. Though a departure from specific features of Japanese haiku such as kigo (season words), sensitivity to the seasons and simple expression techniques, Vietnamese haiku has developed its own variations. The purpose of this study is to highlight the characteristics of Vietnamese haiku with excerpts from representative poems. Whether or not it employs the 5-7-5 structure or seasonal words, there is no doubt that haiku has increased in popularity and enjoyment in Vietnam.